The Impact of Remittances of Migrant Workers onEconomic Growth in Jordan:Econometric Study for the Period 2000 - 2018 Using ARDL Methodology - Al. Nsour, Iyad; Al-Nsour, Ibrahim (The Arab Journal of Administration, 2021)
Remittances is one of the most important sources of foreign currencies for many countries worldwide. The importance of remittances in the economy because of the high value added compared to other cash inflow resources such as grants, exports and foreign direct investment. Therefore, this study aims to measure the economic impact of remittances of Jordanians expatriates on economic growth in Jordan during the period 2000 - 2018, taking into consideration the comparative impact of foreign direct investment, human development and economic openness indicators. An econometric model is designed and it includes the natural logarithm of GDP as a measure of economic growth, in addition to the explained variables which are the remittances and foreign investment as a percentage of GDP, human development and economic openness indicators using the ARDL methodology. The study concludes that the remittances of Jordanian migrant and foreign direct investment have no significant effect on the economic growth, while the human development index has a significant impact in the short-term only. The economic openness is the only variable has a significant impact on economic growth in Jordan on the long and short terms. The study suggests a set of recommendations to enhance the economic policies to exploit the cash inflows such as remittances and FDI and improve their contribution to the local economy.